BIODEGRADATION OF DIESEL OIL BY YEAST ISOLATED FROM MANGROVE’S RHIZOSPHERE - Ryan Firman Syah; Agus Irianto; Nuniek Ina Ratnaningtyas (Fakultas Biologi | Universitas Jenderal Soedirman, 2018)
Diesel oil-degrading yeast strains isolated from mangrove rhizosphere at Tritih Kulon, Cilacap had been screened with SMSS medium. Four culturable yeast were isolated. Qualitative test was conducted by culturing and incubating the yeasts for one month in a medium added with 1mL diesel oil. By measuring the reduction of diesel oil, two best yeasts were selected. The quantitative test, GC-MS analysis, was conducted to determine the detailed degradation process of diesel oil. Candida lusitaniae and Cryptococcus laurentii performed the degradative ability. Three highest percent area of hydrocarbon compounds were compared for assessment. The results showed that C. lusitanie had better degradative capability than C. laurentii, in which hexadecane and methyl hexadecanoate decreased by 90–95%, and 9-octadecenoic acid, methyl ester declined by 30–40%. The increasing pH medium during incubation suggested that fermentation process occurred.